EVALUASI SISTEM PENGUKURAN KINERJA KANTOR PELAYANAN PERBENDAHARAAN NEGARA (STUDI PADA KPPN YOGYAKARTA) - Dian Pustakawan (ABIS: Accounting and Business Information Systems Journal, 2013)
This study aims to evaluate peformance measurement system (PMS) in state treasury office (KPPN) Yogyakarta. Using data gathered from document review and interview with chief and staff of KPPN Yogyakarta, it was found that PMS using Balanced Scorecard in KPPN had accurately measured performance both organization and individual. In contrary, the implementation of PMS had not been used optimaly.